A neglected chapter on Handl's sources: readings from the Swedish manuscripts - Desmet, Marc (De musica disserenda, 2015)
Swedish libraries preserve an important amount of manuscript copies of Jacob Handl compositions. Specificities of the repertory are examined in this article, in relation with written evidence that Handl music had found its way already at an early date within the musical practice of Lutheran Church in Sweden.